Pengaruh Gaya Kepemimpinan dan Komitmen Organisasi Terhadap Kinerja Pegawai Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Karawang - Simbolon, Adi Saputra Pujianto; Hermana, Cecep (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to test and analyze the effect of Leadership Style and Organizational Commitment on Employee Performance of Public Works and Spatial Planning Karawang Regency. This study uses a quantitive method with a descriptive and verification approach. Research samples were gathered using the probability sampling technique with nonrandom sampling which then produced 115 sample of employees who have the status of civil cervant. The research instruments used were observation, interviews and questionnaires. In this study using SPSS 25 analysis tool. Data analysis technique using multiple linear regression test, hypothesis testing using t test. The results of this study show that there is a partial effect of Leadership Style on Employee Performance which has a value of 40.6%, while the partial effect of Organizational Commitment on Employee Performance is 59.4%. The simultaneous effect of Leadership Style and Organizational Commitment on Employee Performance obtained a value 58.7% and the remaining 41.3% was influenced by other variables not examined.